2004
DOI: 10.1029/2003ja010171
|View full text |Cite
|
Sign up to set email alerts
|

Dawn‐dusk asymmetry of geosynchronous magnetopause crossings

Abstract: [1] Geosynchronous magnetopause crossing (GMC) data were collected from literature sources from 1967 and from the experimental data on magnetic measurements on GOES (129 GMCs) and plasma measurements on LANL (197 GMCs) geosynchronous satellites in 1994 to 2001. The dawn-dusk asymmetry of the magnetopause at geosynchronous orbit was examined by two independent methods using the collected data set of 515 GMCs. First, the large amount of accumulated GMCs permitted the revealing of a substantial dawn-dusk asymmetr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 25 publications
6
49
0
Order By: Relevance
“…This asymmetry was also mentioned in Carter et al [2011], where they found that the empirical model fitted better in the dawnside. This dawn-dusk asymmetry could be related to the known asymmetries in either the magnetosheath plasma conditions [e.g., Walsh et al, 2012] or magnetopause position [e.g., Dmitriev et al, 2004], indicating that this asymmetry needs to be considered during the modeling process.…”
Section: Positional Accuracymentioning
confidence: 99%
“…This asymmetry was also mentioned in Carter et al [2011], where they found that the empirical model fitted better in the dawnside. This dawn-dusk asymmetry could be related to the known asymmetries in either the magnetosheath plasma conditions [e.g., Walsh et al, 2012] or magnetopause position [e.g., Dmitriev et al, 2004], indicating that this asymmetry needs to be considered during the modeling process.…”
Section: Positional Accuracymentioning
confidence: 99%
“…[4] Apart from some debate related to the presence of an indentation at high latitudes near the polar cusps [Zhou and Russell, 1997;Dunlop et al, 2000;Lavraud et al, 2002Lavraud et al, , 2004Zhang et al, 2007] and dawn-dusk asymmetries [Dmitriev et al, 2004;Suvorova et al, 2005;Nishino et al, 2008], the shape of the magnetopause is often assumed to be axisymmetric about the aberrated Sun-Earth line, i.e., circular. This hypothesis has been used in most empirical models of the magnetopause [e.g., Sibeck et al, 1991;Petrinec and Russell, 1996;Shue et al, 1997;Kawano et al, 1999], although models using Artificial Neural Network techniques [Dmitriev and Suvorova, 2000] or fits to asymmetric shapes from theoretical expectations [e.g., Zhuang et al, 1981;Boardsen et al, 2000] have also been devised (cf.…”
Section: Introductionmentioning
confidence: 99%
“…Discussing possible drivers of the asymmetry, Dmitriev et al (2004Dmitriev et al ( , 2011 showed convincingly that asymmetries in the upstream solar wind drivers, such as IMF orientation along/orthogonal the Parker spiral, were unlikely responsible for the dawn-duskward asymmetry of the magnetopause at geosynchronous orbit. Orientation of the IMF during geosynchronous magnetopause crossings is totally different from either Parker or ortho-Parker spiral, which are usually exhibited for the undisturbed solar wind.…”
Section: Discussionmentioning
confidence: 99%
“…The dawn-dusk asymmetry in the shape of dayside magnetopause has been convincingly shown on the basis of geosynchronous magnetopause crossings (GMCs) (Dmitriev et al 2004). They found that the GMCs occur most often in a prenoon sector.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation